Patient experiences in intensive care units: a systematic review - Serpil Topçu; Şule Ecevit Alpar; Bilgi Gülseven; Ayda Kebapçı (The Beryl Institute, 2017)
The aim of this systematic review is to analyze the data gathered from studies conducted to determine patient experiences in intensive care and levels of the recollection of the intensive care period that were published between December, 1998 - April, 2013. The systematic review was carried out screening of the related publications. The findings of the systematic review were studied under the following two titles: "remembering the intensive care period" and "recalled experiences" of patients. Studying 15 papers which were found suitable to the inclusion criteria of the review indicated that majority of the patients had recollection of the intensive care process. The physical experiences of the patients were pain, sleep disturbances, discomfort, inactivity or over-activity, noise, thirst, headache, discomfort due to the endotracheal tube (ET), technological support, medical activities, and difficulties in aspiration and swallowing. On the other side, psychological experiences were hallucination, nightmares, fear, worry, anxiety, depression, loneliness, and thoughts about death, panic, nervousness, uncertainty, and despair. In addition, it was seen that patients experienced some communication difficulties. As a result of the systematic review, it was seen that patients could remember the intensive care period, and the number of negative experiences in intensive care were more than the positive ones.